Studi fenomenologi kepuasan kerja pengemudi ojek online - Putra, Afif Andhika; Himam, Fathul; Kusumastutie, Naomi Srie (Mediapsi, 2022)
Ojek online (online motorcycle taxi) is a form of transportation service in Indonesia. This business absorbs millions of workers. However, there are indications of a lack of job satisfaction among the drivers. The lack of job satisfaction may hinder the drivers' performance and services. In the present research, we explore what job satisfaction means among online motorcycle taxi drivers. We collected the data by interviewing three drivers. We then analyzed the data using the Interpretative Phenomenological Analysis (IPA) method. The results suggest that the drivers interpret their job satisfaction in terms of freedom, sufficiency, and harmony. Online motorcycle taxi companies can use the current findings when implementing their policy. Ojek online adalah salah satu bentuk layanan transportasi di Indonesia. Bisnis ini menyerap jutaan tenaga kerja. Namun, ada indikasi kurangnya kepuasan kerja di antara para pengemudi. Kurangnya kepuasan kerja dapat menghambat kinerja dan pelayanan pengemudi. Dalam penelitian ini, kami mengeksplorasi apa arti kepuasan kerja di kalangan pengemudi ojek online. Kami mengumpulkan data dengan mewawancarai tiga pengemudi. Kami kemudian menganalisis data menggunakan metode Interpretative Phenomenological Analysis (IPA). Hasilnya menunjukkan bahwa pengemudi menafsirkan kepuasan kerja mereka dalam hal kebebasan, kecukupan, dan keharmonisan. Perusahaan ojek online dapat menggunakan temuan saat ini ketika menerapkan kebijakan mereka.